DNA Barcoding on Indian Ocean Squid, Uroteuthis duvaucelii (D'Orbigny, 1835) (Cephalopoda: Loliginidae) from the Java Sea, Indonesia - Norma Afiati; Subagiyo Subagiyo; Christina Retna Handayani; Retno Hartati; Nenik Kholilah (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research • The possibility of U. duvauceli be a polymorph cryptic species is further reinforced by the results of the present study. • Phylogenetic analysis showed two separate clusters though did not perfectly segregate north to the south waters. • Individuals in cluster II from the south coast showed the highest polymorphism levels by 40 segregating sites (S), compared to only 2-4 sites in that of cluster I • Frequencies of A, C, G, and T in mitochondrial DNA of all specimens skewed toward A and T, with T being the most preferred and G being the least preferred nucleotide • All specimens showed no amino acid frequency for glutamic acid. Further, all four individuals in cluster II (south coast) were also have no amino acid frequencies for aspartic acid and valine as well.